2004
DOI: 10.4049/jimmunol.172.7.4470
|View full text |Cite
|
Sign up to set email alerts
|

CD14 Is an Acute-Phase Protein

Abstract: The origin of soluble CD14 (sCD14) in the circulation is uncertain. To examine whether CD14 could be an acute-phase protein (APP), the levels of sCD14, IL-6, and C-reactive protein were determined by ELISA in serum and synovial fluid (SF) of patients with various arthropathies, and the regulation of CD14 synthesis was examined in liver cells. In patients with crystal-mediated or immunologically mediated arthritis (rheumatoid arthritis), serum levels of sCD14 were higher than or similar to those found in infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
209
3
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(237 citation statements)
references
References 83 publications
13
209
3
8
Order By: Relevance
“…However, because of its abundance in the serum, the idea that the sole function of CD14 is to serve as the LPS uptake protein has been frequently challenged and an alternative model, in which an excess of sCD14 facilitates its protective functions by binding with LPS, has been proposed [21]. Furthermore, correlation of serum levels of sCD14 with disease activity in rheumatoid arthritis patients suggests that sCD14 can be considered an acute-phase protein [9]. Our findings support this hypothesis, since we observed a remarkable elevation of sCD14 in the serum of LPSprimed transgenic mice and in macrophages in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of its abundance in the serum, the idea that the sole function of CD14 is to serve as the LPS uptake protein has been frequently challenged and an alternative model, in which an excess of sCD14 facilitates its protective functions by binding with LPS, has been proposed [21]. Furthermore, correlation of serum levels of sCD14 with disease activity in rheumatoid arthritis patients suggests that sCD14 can be considered an acute-phase protein [9]. Our findings support this hypothesis, since we observed a remarkable elevation of sCD14 in the serum of LPSprimed transgenic mice and in macrophages in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble CD14 (sCD14) is present in the serum of normal adults at a concentration of *1 lg/mL and is significantly elevated during septic shock [8]. Such high levels of sCD14 suggest that in addition to mediating signaling from LPS, sCD14 may function as an acutephase protein or have other functions [9]. Several attempts have been made to over-express sCD14 in vivo under control of a heterologous promoter in order to examine its possible protective role in LPS-initiated endotoxin shock [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Endotoxin concentrations as low as 1 pg/ml could induce cellular activation and expression of CD14 (20,21). Recent evidence indicates that sCD14 may be derived by enzymatic cleavage of glycosylphosphatidylinositol-anchored cell membranebound CD14 or secreted by liver in response to inflammation or infection (22). Interestingly, sCD14 can both potentiate and downregulate responses to LPS by transfer of LPS to lipoproteins for subsequent removal (23).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies reported serum levels of CD14 elevated in inflammatory conditions, such as Kawasaki disease, atopic dermatitis, liver disease, rheumatoid arthritis (RA), systemic lupus erythaematosus, primary Sjogren's syndrome and Periodontitis. Recently, sCD14 is demonstrated as a regulatory factor capable of modulating cellular and humoral immune responses by interacting directly with T and B cells [27].…”
Section: Cd14mentioning
confidence: 99%